2012
DOI: 10.3945/jn.112.160416
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Concentrations and Metabolic Syndrome Are Associated among U.S. Adolescents in Recent National Surveys

Abstract: Specific micronutrients, including retinol, retinyl esters, carotenoids [α-carotene, β-carotene (cis+trans), β-cryptoxanthin, lutein+zeaxanthin, and total lycopene], vitamin E, and vitamin C have antiinflammatory and antioxidant effects, properties shown to reduce oxidative stress, a process that accompanies the pathogenesis of many chronic diseases. It is still largely unknown whether they are associated with the occurrence of metabolic syndrome (MetS) in the adolescent U.S. population. MetS was defined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 104 publications
6
77
0
5
Order By: Relevance
“…Changes in oxidized low density lipoprotein (oxLDL) levels were inversely correlated with plasma lutein [7] , and an increase in BMI among the population was significantly associated with low levels of serum lutein [8] . Insulin resistance was also found to be inversely related to serum lutein levels [9][10][11] . To date, there have been very few reports regarding the mechanism and effects of lutein on NAFLD, or on the risk factors of NAFLD.…”
Section: Introductionmentioning
confidence: 91%
“…Changes in oxidized low density lipoprotein (oxLDL) levels were inversely correlated with plasma lutein [7] , and an increase in BMI among the population was significantly associated with low levels of serum lutein [8] . Insulin resistance was also found to be inversely related to serum lutein levels [9][10][11] . To date, there have been very few reports regarding the mechanism and effects of lutein on NAFLD, or on the risk factors of NAFLD.…”
Section: Introductionmentioning
confidence: 91%
“…Only one of these studies assessed dietary intake (4) , and all the other studies used blood levels of lutein. In addition, the only study in adolescents that assessed lutein intake in relation to cardiometabolic health used blood levels of lutein, and observed that higher lutein levels were associated with a lower metabolic syndrome score (11) . As compared with the use of dietary intake levels, the use of blood levels of lutein might provide a more direct measurement of how much lutein is available.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one article has been published so far that related lutein to cardiometabolic health in children (11) . In this cross-sectional study among 1339 US adolescents, lutein levels were not significantly associated with metabolic syndrome diagnosis, but higher level of lutein was significantly inversely associated with a continuous score of a number of metabolic syndrome components.…”
mentioning
confidence: 99%
“…The Panel is aware of other studies which looked at possible associations between preformed vitamin A intake or blood retinol concentration and adverse health outcomes (Grotto et al, 2003;Bjelakovic et al, 2008;Chen et al, 2008;Mayo-Wilson et al, 2011;Beydoun et al, 2012;Bjelakovic et al, 2012;Bjelakovic et al, 2013;Field et al, 2013;Bjelakovic et al, 2014). Available data on individual outcomes are limited or relate to interventions that used large doses of retinol (≥ 6 000 µg) once or several times a year, which are difficult to relate to a potential effect of daily dietary intake of retinol.…”
Section: Excessmentioning
confidence: 99%